Object-parameter approaches to predicting unknown data in an incomplete fuzzy soft set - Liu, Yaya; Qin, Keyun; Rao, Chang; Alhaji Mahamadu, Mahamuda (Zielona Góra: Uniwersytet Zielonogórski)
The research on incomplete fuzzy soft sets is an integral part of the research on fuzzy soft sets and has been initiated recently. In this work, we first point out that an existing approach to predicting unknown data in an incomplete fuzzy soft set suffers from some limitations and then we propose an improved method. The hidden information between both objects and parameters revealed in our approach is more comprehensive.
Keywords: fuzzy soft set; incomplete fuzzy soft set; object-parameter approach; prediction; similarity measures